2023
DOI: 10.1002/pan3.10449
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling diverse viewpoints within systematic conservation planning

Abstract: Conservation encompasses numerous alternative viewpoints on what to value (features suchas biodiversity, ecosystem services or socio-economic benefits) and how to convert these values into conservation policies that deliver for nature and people. Reconciling these differing values and viewpoints in policy development and implementation is a perennial challenge. 2. Balancing differing stakeholder viewpoints within a single conservation plan risks some viewpoints overshadowing others. This can occur as some domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Researchers have found that PPGIS can explore these correlates when used as part of a suite of methods (Elwood, 2010) Also beyond the scope of this paper was a comparative analysis between people's spatial perception of risk and the projected climate risks (Brown et al, 2004). Since the local council has exclusively relied on projected risks for management and planning decisions, identifying areas where there is a high perception of risk and low projected risk, and vice versa, could assist local governments in reducing con ict between stakeholders and decision-makers (Carmen et al, 2022;Cunningham et al, 2023). Additionally, this paper discussed the role of the land management authority, which can limit the potential scope or ambition of local adaptation actions due to ambiguity or contestation over jurisdiction.…”
Section: Future Research Opportunitiesmentioning
confidence: 99%
“…Researchers have found that PPGIS can explore these correlates when used as part of a suite of methods (Elwood, 2010) Also beyond the scope of this paper was a comparative analysis between people's spatial perception of risk and the projected climate risks (Brown et al, 2004). Since the local council has exclusively relied on projected risks for management and planning decisions, identifying areas where there is a high perception of risk and low projected risk, and vice versa, could assist local governments in reducing con ict between stakeholders and decision-makers (Carmen et al, 2022;Cunningham et al, 2023). Additionally, this paper discussed the role of the land management authority, which can limit the potential scope or ambition of local adaptation actions due to ambiguity or contestation over jurisdiction.…”
Section: Future Research Opportunitiesmentioning
confidence: 99%